MANCA: Health calculator, food and exercises mobile application / Muhammad Nabil Isyraff Mohd Isyam - Mohd Isyam, Muhammad Nabil Isyraff (2022)
In this era of modernization, despite significant scientific evidence supporting the advantages of regular exercise in the prevention and treatment of cardiovascular disease (CVD), physical inactivity is extremely common across the world. Having a healthy lifestyle is important to maintain overall health status. For this project, a mobile application is developed to calculate the Body Mass Index (BMI), Total Daily Energy Expenditure (TDEE) and Basal Metabolic Rate (BMR). The objective of this project is to identify the system requirement, to design and to develop Manca Mobile Application The aim of this project is to develop Manca with features of automated calculation that can can calculate BMI, BMR and TDEE and based on TDEE and BMR result can calculate the calories intakes the user needs. The methodology used is the Mobile Software Development Lifecycle (MSDLC) until the testing phase. The Manca Mobile Application is developed on Android platform. Offering such as features are the (type of calculator), search features on food list and list of exercise video. Based on the result after the testing phase, overall System Usability Score has high perceived usability, with System Usability Score of 76.14. The future direction is to implement an algorithm that can recommend food and exercise based on the user calories and preferences.